Coronavirus disease 2019 (COVID-19) outbreak during a Chinese New Year dinner in a restaurant, Hong Kong Special Administrative Region SAR (China), 2020 (Western Pacific Surveillance and Response, 2021)
We reported a local family cluster of 6 confirmed COVID-19 cases among 29 attendees of a Chinese New Year family dinner gathering in a restaurant, with 1 additional case from secondary transmission. This report illustrates that the public should maintain physical distancing during the COVID-19 pandemic.